98.2k views
3 votes
What is the value of y in the following system of equations? explain how you found your answer

What is the value of y in the following system of equations? explain how you found-example-1
User Qsantos
by
4.7k points

2 Answers

9 votes
2x + 3y = 6
2x + y = -2

Solve the second equation for y and substitute into the first equation

2x + y = -2
y = -2x - 2

2x + 3y = 6
2x + 3(-2x - 2) = 6
2x - 6x - 6 = 6
-4x - 6 = 6
-4x = 12
x = -3

Plug back in to solve for y
2x + y = -2
2(-3) + y = -2
-6 + y = -2
y = 4

Plug into other equation to check
2x + 3y = 6
2(-3) + 3(4) = 6
-6 + 12 = 6
6 = 6 :)
User Just Somebody
by
4.3k points
3 votes

Explanation:

I've used elimination method over here but it can also be done by using substitution.

What is the value of y in the following system of equations? explain how you found-example-1
User Svgrafov
by
5.0k points